Intelligent Home and Office LED Lighting System Considering Energy Efficiency and Environmental Conditions - L, Nishanth; k, Nirmalakumari (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Saving electrical energy has become one of the most important problem facing in now a days . The most waste of energy is caused by the inefficient use of the user electronic devices. specifically a light accounts for a great part of the total energy consumption. many light control systems are introduced in light system market, because the installed lighting systems are out-dated and more energy consumption. because of the reason of architectural limitations, the existing light control systems consume more power in home and office buildings lightning system. Therefore, this paper proposes an intelligent home and office LED lighting system with energy efficiency and user environment. The proposed system utilizes multi sensors and wireless communication technology to control an LED light according to the user’s location and the surroundings. The proposed LED lighting system can automatically adjust the minimum light intensity value to enhance both energy efficiency and user convenient. We designed and implemented the proposed system in the test bed and measured total power consumption to verify the performance